Analisis Kebijakan Transformasi RASTRA Menjadi BPNT Sebagai Upaya Penanganan Kemiskinan - Gustin, Gustin (Mawaizh : Jurnal Dakwah dan Pengembangan Sosial Kemanusiaan, 2019)
The complex poverty paradigm is no longer interpreted in the concept of economic incompetence but is also a failure to fulfill one's basic rights. The emergence of the conception of poverty raises the powerlessness of individuals or groups of people to become prosperous individuals for the sake of welfare. In the framework of implementing the Literature Food and Social Protection Program and National Land Agency, harmonization and synergy between institutions at the central level or between institutions / OPD at the regional level and related parties are needed so as to produce effective results. Transformation of Literature into BPNT for a region requires several optimal prerequisite analyzes, one of which is signal optimization and special differences in difficult areas.